Investigation into the time characteristics of the volleyball game - Kountouris, P; Laıos, J (Coaching Volleyball, 2000)
This article focused on the investigation of the time characteristics of individual sets of volleyball matches in relation to their order in the match, the total number of sets in the game, the category of the teams and the sex of the players in two consecutive years, before and after the enforcement of the new regulations. All the matches from the corresponding leagues in Greece for 1997-1998 and 1998-1999 were taken into consideration giving a total of 1016 games. Besides the obvious conclusion that sets from games with a 3-0 final score are smaller in duration than sets form games with a 3-1 or 3-2 final score, it seems that the professionalism of the teams playing a volleyball match bears a strong relevance to set duration characteristics and interdependencies. Professional teams are able to display a more consistent performance throughout all the sets of the game. Based on the present inferences, as well as taking into consideration the requirements of a more rigorous presence of volleyball in the TV, where the time fluctuations of the duration of a volleyball match should be eliminated, it is proposed that the game of volleyball should be played with a fixed number of sets and that this number should be equal to four.   Keywords: Volleyball, match duration, set duration.